Sempah Volcanic Complex, Western Belt of Peninsular Malaysia. Preliminary Study of Petrology and Geochemistry - A Ghani, Azman; Navpreet, Singh (Malaysian Journal of Science, 2002)
The Sempah volcanic complex occupies the central part of the Main Range Batholith to the east of Kuala Lumpur. The complex intruded the Selut Schist (Pre Ã¢â‚¬â€ Devonian), Gombak Chert (Late Devonian Ã¢â‚¬â€ Early Carboniferous, Sempah Conglomerate (Permian) which were collectively known as the Bentong Group. The complex consists of two main rock types namely rhyodacite and orthopyroxene rhyodacite. Geochemical evidence indicate that the rhyodacite and orthopyroxene rhyodacite are not related by simple fractional crystallization. The difference is indicated by a compositional gap at 69.1 to 70.7% $Si0_2$, different ACNK values, different ACNK trends, with increasing $Si0_2$ and contrasting behaviour for the major and trace elements, particularly $K_{2}0$ and $Ba$. This is supported by major element modelling where both rhyodacite and orthopyroxene rhyodacite have different mineral extract proportions.